3u+7=-5

Simple and best practice solution for 3u+7=-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3u+7=-5 equation:


Simplifying
3u + 7 = -5

Reorder the terms:
7 + 3u = -5

Solving
7 + 3u = -5

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + 3u = -5 + -7

Combine like terms: 7 + -7 = 0
0 + 3u = -5 + -7
3u = -5 + -7

Combine like terms: -5 + -7 = -12
3u = -12

Divide each side by '3'.
u = -4

Simplifying
u = -4

See similar equations:

| 0.5(-4+6x)=33.3x+66.6(x+9) | | 15x-5=1+12x | | 25x*76= | | 2-3a=7-2(2a+3) | | 7x+6(-x-17)=-109 | | -8(m-8)=120 | | 7x+.43=y | | -9x+4=-6x+17 | | 12x-8=6x+22 | | 7x-6x-102=109 | | 2x+116-116=180-116 | | 7x-(3x+4)=-2(2x-1)+10 | | 2x^4+x^3-9x^2-4x+4=0 | | 97=4(2+3k)+5 | | 5y-3=8+4(y-2) | | 2(9.2-8)+2(9.2-8)= | | 3d-8=7+8d | | -29=5(2x-1)+2a | | t-12=-4 | | 17-3p=16-4 | | 9x+13-5x=-8x-30+x | | 4(2+3x)=56 | | 2(9.2-8)+2(9.2-8)+9.2= | | 4.05+14.4=4.5(p+3) | | 3(x+65)+3x=2595 | | 8(8-4r)=160 | | 9x+3=4x-9 | | 3r=-11/9 | | 6(5x+6)=30x-3 | | 3x+5=7x+4 | | 10x-2=7x-7.4 | | -6x=12y+72 |

Equations solver categories